2015
DOI: 10.3389/fpsyg.2015.01245
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of mother–child feeding interactions in preterm and term dyads at 18 and 24 months

Abstract: Literature on mother–child feeding interactions during the transition to self-feeding in preterm populations is lacking, particularly through observational methods. The present research study aims to look at the longitudinal patterns of mother–toddler feeding interactions, comparing preterm and full term dyads. To this end, a multi-method approach was used to collect data from 27 preterm to 20 full-term toddlers and their mothers. For each dyad, mother–child interactions were observed during the snack time at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 86 publications
0
3
0
2
Order By: Relevance
“…Both the maternal psychological discomfort and the immature behavior of late preterm infants could hinder the interaction of the dyad, thus favoring a conflictual approach during feeding [28,[41][42][43]. Salvatori et al [42] showed that preterm dyads had fewer positive interactions during feeding times at 18 and 24 months than term dyads; moreover, preterm infants had increased food refusal behaviors from 18 months to 24 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the maternal psychological discomfort and the immature behavior of late preterm infants could hinder the interaction of the dyad, thus favoring a conflictual approach during feeding [28,[41][42][43]. Salvatori et al [42] showed that preterm dyads had fewer positive interactions during feeding times at 18 and 24 months than term dyads; moreover, preterm infants had increased food refusal behaviors from 18 months to 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…Both the maternal psychological discomfort and the immature behavior of late preterm infants could hinder the interaction of the dyad, thus favoring a conflictual approach during feeding [28,[41][42][43]. Salvatori et al [42] showed that preterm dyads had fewer positive interactions during feeding times at 18 and 24 months than term dyads; moreover, preterm infants had increased food refusal behaviors from 18 months to 24 months. In line with these findings, Yatziv et al [43] showed that mothers of preterm infants experienced higher emotional distress than full-term mothers, were less responsive to their infant's hunger cues, showed a more intrusive attitude, and left their infants less autonomy feeding than mothers of term ones.…”
Section: Discussionmentioning
confidence: 99%
“…Parents with higher levels of anxiety or depression may find it more difficult to read their child's feeding cues, provide appropriate mealtime structure and cope when presented with medical conditions that impair feeding [21] . Research undertaken with ex-preterm toddlers found mothers with higher anxiety or depression were more controlling and intrusive in their mealtime interactions, hindering their child's independent feeding and this was associated with higher toddler distress, avoidance of eating and negative mealtime behaviours [25] . A recent study found 42% of children with OA/TOF presented with a feeding disorder, displaying oppositional and aversive behaviours causing stressful mealtimes [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Экзогенно-конституциональное ожирение, а также часто сопутствующие ему метаболические сдвиги (дислипидемии, инсулинорезистентность) в основе своей могут иметь первичные нарушения пищевого поведения (ПП), приводящие к несоответствию объема питания и энергозатрат. Недоношенность может влиять на проблемы в питании с точки зрения нарушений физиологических процессов в раннем периоде жизнитрудностей в развитии навыков кормления, неудач в грудном вскармливании, дисфагии в раннем возрасте, кроме того, есть данные о том, что существует повышенный риск развития расстройств ПП у лиц, родившихся преждевременно [1]. Хотя связь между недоношенностью и расстройствами ПП во взрослом возрасте все еще спорна [2], следует отметить, что проблемы с питанием в детском возрасте сами по себе могут сохраняться и влиять на долгосрочный риск расстройств ПП, таких как булимия и анорексия, а также на эмоциональные и поведенческие проблемы во взрослом возрасте [3].…”
Section: обоснованиеunclassified